President's Message - McLeod, Bonnie (Operating Room Nurses Association of Canada Journal, 2010)
Ten provincial representatives, three affiliate representatives, five executive members and the executive director were all invited to attend an ORNAC strategic planning session from August 27-29, 2010 in Ottawa, ON. The purpose of this meeting was to bring together experts in the field of perioperative nursing practice in order to work through a strategic planning process that included analysis, discussion, debate, and strategizing and planning for the future of ORNAC.